The Influence of Work Culture and Job Satisfaction on the Performance of Health Workers at the Bontomarannu Public Health Center, South Galesong District - Irnawati; Sri Andayaningsih; Zalkha Soraya (Journal AGENCY, 2026)
This study aims to determine how the influence of work culture and job satisfaction on the performance of health workers at the Bontomarannu Community Health Center, South Galesong District. This study is a quantitative study. The data for this study were obtained through observation and questionnaires. The population in this study was 50 health workers using the Slovin formula. The data used the Multiple Linear Regression method, Normality Test, Multicollinearity Test, Heteroscedasticity Test, T Test, F Test, and Coefficient of Determination using SPSS 26 software. Based on the results of the study, work culture has a significant positive effect on performance, meaning that the better the work culture implemented, the better the performance of health workers will be. Likewise, job satisfaction has a significant positive effect on the performance of health workers, meaning that health workers who are satisfied with their work will have higher work enthusiasm, greater responsibility, and a strong commitment in carrying out their duties. And work culture and job satisfaction simultaneously have a significant positive effect on the performance of health workers, meaning that work culture and job satisfaction together have a significant effect on the performance of health workers at the Bontomarannu Community Health Center UPT, South Galesong District. Work culture and job satisfaction are important factors in improving employee performance, because both are able to shape the attitudes, motivation, and work behavior of health workers in carrying out their duties and responsibilities.